(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
The present study was undertaken to assess the allelopathic effect of Chrysanthemum procumentens in relation to germination and growth of bean seedling. C. procumentens reduced germination and suppressed early seedling growth of beans. With increase in extract concentration from 20 mg ml-1 to 60 mg ml-1, a gradual decrease in seed germination evaluated by reduction in the concentration of biomolecules such as total protein, total soluble sugar and amylase activities; and increase in the activities of hydrolytic enzymes such as proteases, Lipases and Arginase occurred. The longest seedling root and shoot lengths were recorded on day 1 at 20 mg ml-1 extract concentration while the shortest seedling root and shoot length were recorded on day 6 at 80 mg ml-1 extract concentrations. It was noted that the reduction in germination and suppression of seedling growth observed in this study were concentration and time dependent. The result suggested that C. procumentens had good allelopathic potential which reduces germination and plant growth.